The Effects of Family Planning Methods Used Among Women in Turkey on Depression, Anxiety and Stress Levels - Barut, Sümeyye; Güney, Esra; Ucar, Tuba (My University, 2022)
Objective: This study was planned to determine the effects of family planning methods used among women in Turkey on depression, anxiety and stress. Materials and Methods: This descriptive and comparative study was carried out with 453 married women using an online survey. The data were collected using a “Personal Information Form” and the “Short Form of the Depression, Anxiety and Stress Scale”. Results: In the study, it was determined that the stress and anxiety levels of the women who used one of the hormonal contraceptive, intrauterine device, condom and tube ligation methods were lower than the levels of the women who did not use any method. The stress and anxiety levels of the women who did not use any family planning method or used traditional methods were higher than any of the modern methods. Conclusion: It may be stated that the provision of counseling about modern family planning methods for women and their spouses by midwives and nurses can reduce mental problems that could result from the use of family planning methods.
Keywords: Anxiety; depression; stress; Women; family planning